Is It Time We Changed How We Measure Length of Stay for Hip and Knee Arthroplasty? - McCulloch, Robert (J Am Acad Orthop Surg Glob Res Rev, 2017)
INTRODUCTION: Patient length of stay (LOS) for lower limb arthroplasty is a frequently quoted outcome measure. However, the use of mean values in days is prone to being skewed by outliers. METHODS: Between January 2013 and December 2015, patient LOS for primary hip and knee replacement was collected in 1,168 patients. There were two groups: pre- and postinstitution of the Rapid Recovery Program. The hypothesis was that reducing LOS would highlight proportionate differences when using hours as the measuring unit. RESULTS: Statistical analysis confirmed a significant reduction in LOS between the Enhanced Recovery Program and Rapid Recovery Program (P < 0.001). DISCUSSION: Use of the median LOS reduces the impact of outliers. Use of hours as the unit of measure of LOS enabled analysis of the time of day of discharge. With decreasing LOS and day-case arthroplasty, a measurement in median hours should become the standard to allow for the detection of subtle changes.